ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS WESBITE, DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN SERTA DAMPAKNYA TERHADAP LOYALITAS KONSUMEN (Studi pada Konsumen E-commerce B2C Berrybenka di Semarang) - Nabilah, Beby Pamungkas; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2018)
This research is motivated by the decrease in the number of visitors on Berrybenka site and complaints from customers which indicate dissatisfaction toward Berrybenka that can affect the loyalty of Berrybenka’s customers. Based on the problems, this research aimed to examine the effect of product quality, website quality, and service quality to customer satisfaction and its impact on customer loyalty. This research was conducted at e-commerce B2C Berrybenka site.The sample of this research is 100 respondents who had ever done purchase transaction on e-commerce B2C Berrybenka site at least 2 times and stay in Semarang. This research consisted of 5 variables, 19 indicators, and 5 hypothesis. The analysis instrument used was SPSS 22 with multiple linear regression and sobel test as analysis methods to examine the indirect effect of independent variables to dependent variable through intervening variable.The result of this research showed that product quality has positive and significant effect on customer satisfaction, website quality has positive and significant effect on customer satisfaction, and service quality has positive and significant effect on customer satisfaction with result Y1= 0,360X1 + 0,263X2 + 0,348X3. Customer satisfaction has positive and significant effect on customer loyalty with result Y2= 0,896Y1. The result of sobel test showed that product quality, website quality, and service quality have indirect effect on customer loyalty through customer satisfaction